A Combination Therapy for Diabetes Miletus Using Metformin Hydrochloride and Gliclazide Bilayer Tablets - Rajeswari Aleti; Sailaja Gunnam; Monika Nijhawan (Pharmaceutical Research - Recent Advances and Trends Vol. 4, 2024)
Objective: The main objective of the present investigation is to develop combination therapy for Type II Diabetic subjects using bilayer sustained release formulation of metformin hydrochloride (MFH) and gliclazide (GLZ) based on monolithic-matrix technology. Methods: Bilayer tablets were prepared by the wet granulation method. Initially, metformin HCl layer and gliclazide layers were optimized using release retardants like Polyox WSR coagulant and different viscosity grades of hydroxyl propyl methyl cellulose (HPMC) and evaluated for in vitro dissolution performance and drug excipient studies separately. The optimized formulations were selected and compressed to bilayer tablets to achieve the desired sustained release in combination. Results: Metformin hydrochloride and gliclazide showed sustained release of drug by diffusion mechanism and followed first-order kinetics. The best formulation of metformin hydrochloride (M7) and gliclazide (G8) shows 99.93% and 99.65% of drug release in 24 h respectively. The similarity factor (f2) was 89.95 for metformin hydrochloride and 83.62 for gliclazide when compared to the innovator. FTIR studies reveal the absence of significant interactions indicating drug excipient compatibility. Conclusion: The monolith diffusion-controlled bilayer tablets of metformin hydrochloride and gliclazide offer improved patient compliance and convenience with better postprandial hyperglycemic control with once-a-day dosing. The sustained release of the drug up to 24 h regulates antidiabetic activity round the clock with minimal side effects.